Ethnobotanical survey and in vitro quality assessment of Dendrobium thyrsiflorum B. S. Williams from the Ultapani Forest Range, Assam, India - Das , Sangita; Baruah, Sanjib; Goyal, Arvind Kumar (Plant Science Today, 2026)
Dendrobium thyrsiflorum B. S. Williams (Orchidaceae), locally known as ‘Garudi Baha/ Khejari Baha’ by the Santhal community of the Ultapani Forest Range, Bodoland Territorial Region (BTR), Assam. The species occurs anthesis between March and May, with flowers reaching full bloom and attracting pollinators. This study investigated the ethnobotanical uses, macroscopic and microscopic pharmacognostic characteristics, qualitative and quantitative phytochemical composition, heavy metal content, antioxidant activity and volatile compound profile of D. thyrsiflorum. Ethnobotanical surveys conducted among the Santhal community revealed the traditional use of leaves and pseudobulbs as a medicine for the treatment of various gynecological and parasitic ailments. The examination of powdered plant material showed satisfactory organoleptic properties (colour, aroma/odour, flavour/taste and texture) for both leaves and pseudobulbs. Microscopic analysis identified fibers in both leaves and pseudobulbs, parenchyma cells and stomata in leaves and acicular crystals and spiral vessels in pseudobulbs. Aqueous extracts of leaves and pseudobulbs underwent qualitative phytochemical screening, revealing the presence of alkaloids, carbohydrates, glycosides, terpenoids and steroids in both tissues. The heavy metal analysis indicated the absence of bismuth, cadmium and lead in the samples. Quantitative phytochemical analysis determined the total polyphenol content (TPC) to be 27.62 ± 0.03 mg gallic acid equivalents (GAE)/g dry weight in leaves and 17.57 ± 0.02 mg GAE/g dry weight in pseudobulbs. The total flavonoid content (TFC) was measured as 120.36 ± 0.05 mg quercetin equivalents (QE)/g dry weight in leaves and 87.50 ± 0.04 mg QE/g dry weight in pseudobulbs. The antioxidant activity was further evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric ion reducing antioxidant potential (FRAP) assays, demonstrating higher activity for DPPH assay compared to the standard. Gas chromatography-mass spectrometry (GC-MS) analysis identified 88 compounds in leaves and 59 compounds in pseudobulbs. These findings contribute to the establishment of pharmacognostic and phytochemical standards for D. thyrsiflorum, aiding in species identification, quality control and standardization of herbal formulations.